Rapporto dallo spazio profondo - Bernardini, Fabrizio (GEOmedia, 2010)
Report from deep space This instalment of ‘Terra e Spazio' column deals with an update about the status of the exploration of the Solar System. Research programmes, some of them started decades ago, are producing or are going to produce, spectacular results, more often badly divulgated or little appreciated. Behind these programs we find teams of scientists and engineers that are "living” their own mission for years and years. Data products, on their own, will feed scientific research for years, augmenting the knowledge about the planets of our System.